PRE-IRRIGATION WITH GEL HIDRORETENTOR IN EUCALYPTUS SEEDLING ESTABLISHMENT IN THE FIELD - Bernardino, Lynniker Trés; Bonomo, Robson; Souza, Joabe Martins de; Zucoloto, Moises (Floresta, 2019)
Research has sought new technologies aimed at establishing more productive forests. Hidroretentor gel that has the function of increasing the availability of water to the plant, in the most critical stage of establishment of the cuttings in the field. The objective of this study was to evaluate increasing levels of water retention gel applied in pre-irrigation, moments before planting, observing the survival index, and the morphological variables for the hybrid Eucalyptus grandis x E. urophylla-03, in Chapadinha-MA. The experiment was a randomized block with seven treatments and three replicates. The treatments consisted of five increasing doses of 1.0; 2.0; 3.0; 4.0 and 5.0 g 5 L-1 gel solution per liters of pre-irrigation, a treatment without the use of the gel; and a conventional planting treatment. The use of pre-irrigation with hidroretentores polymers, known as hidroretentor gel at a concentration of 4 and 5g 5L-1, provides a greater height, stem diameter, increasing the growth of eucalyptus plants in post-planting. The depth of the root system did not improve when a higher dose of gel was used, obtaining lower values than those obtained by the treatment without the use of the hidroretentor gel.